The applied ethics of emerging military and security technologies - Allenby, Braden R. (Ashgate Publishing Company, 2015)
The essays in this volume illustrate the difficult real world ethical questions and issues arising from accelerating technological change in the military and security domains, and place those challenges in the context of rapidly shifting geopolitical and strategic frameworks. Accordingly, this volume is of interest to students of military or security domains, as well as to those interested in technology and society, and the philosophy of technology.